Health symptoms and the work environment in four nonproblem United States office buildings - Nelson, Nancy A; Kaufman, JD; Burt, J; Karr, C (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'The objective of this study was to quantify health symptom reports in four "nonproblem" buildings and to assess the relationship between symptoms and air quality measures, workstation characteristics, and psychosocial aspects of the workplace.' ' METHODS ': 'Environmental sampling was conducted in four office buildings occupied by employees working for the state of Washington in March of 1992. A questionnaire was concurrently administered to building occupants.' ' RESULTS ': 'While measured contaminant levels were low, symptoms were frequent. Fifty-five percent of the 646 respondents reported recent symptoms which affected the eyes, nose, or throat and improved when away from work. Symptoms were not associated with measured contaminant levels, but, rather, with perceptions about air movement, dryness, odors, and noise. Psychosocial factors were less strongly associated with symptoms.' ' CONCLUSION ': 'Even in nonproblem buildings, symptom reports can be frequent and may represent overall satisfaction with the work environment. In response to symptoms ascribed to air quality problems, it may be appropriate to address employee perceptions regarding the work environment in addition to evaluating environmental characteristics relating to chemicals, biological contamination, air movement, temperature, and humidity.
Keywords: epidemiology; general symptom; indoor air quality; mucosal irritation; office work